Perancangan Buku Fotografi Esai "Hygge" untuk Menarik Minat Wisatawan dan Masyarakat di Kota Malang - Tiffany Yosephine; Didit Prasetyo Nugroho (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2022)
Theemergence of various kinds of cafes in Malang City has created a new lifestyle, namely gathering with friends, especially for the younger generation. This lifestyle makes cafes continue to appear in Malang City with concepts that are liked by this generation, one of which is the cozy concept. But this makes the cafés that keep popping up pay less attention to quality in terms of atmosphere and menu because they focus too much on the cozy interior that the younger generation likes. Therefore, information media is needed that can attract tourists and the public in choosing and visiting cafes not only based on trends, through making designs that aim to get concept visualizations through the media of essay photography books that contain information about 8 cafes with cozy concepts in Malang City. The design method used is the creative communication design method and is combined with qualitative data collection methods. This essay photography book uses interior and food photo styles, with a book size of 22.4 x 17 cm with a total of 248 pages, full color, and bound using doff laminated hardcover. The conclusion of this design is to get a visualization of the concept of an essay photography book to provide information about cozy cafes through photo visualization along with narratives through book media and supporting media such as bookmarks, tote bags, photo sheets, stickers, tumblers, acrylic straws, diffusers, and marketing media through social media Instagram.